Integration of the Transformational Leadership Model with Local Wisdom to Strengthen Organizational Capacity for Change Study at the Tebuireng Islamic Boarding School Jombang - Hikmah Muhaimin; Dhiyan Septa Wihara; Santosa (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2023)
Transformational leadership is a type of leadership that prioritizes the values and beliefs of subordinates. This type of leadership is considered suitable to be implemented in Islamic boarding schools because learning in Islamic boarding schools is based on values which are applied top-down from caregivers to administrators and then to students or santri. This method has been going on for a long time and of course now there needs to be a change because every Islamic boarding school is required to balance the value of religiosity with abilities in general knowledge like schools in general. This is because most parents entrust their children to Islamic boarding schools to educate morals with inherent religious values. So Islamic boarding schools must have the capacity to change their organization or transform into modern Islamic boarding schools that still uphold the values of local wisdom that have been built long ago by their founders. The formulation of the problem in this research is how to integrate the transformational leadership model with local wisdom to strengthen organizational capacity for change in Islamic boarding schools in Jombang, East Java, Indonesia. This research aims to 1) analyze the leadership patterns applied in Islamic boarding schools, 2) analyze the learning process implemented by administrators for students, 3) analyze the impact of changes on students related to religious and conventional knowledge, and 4) measure the readiness of Islamic boarding schools to transform according to with general education standards without abandoning the cultural values passed down from the founders. The approach in this research is qualitative where most qualitative researchers can relate to the value contained in the case study method, so that they are able to explain an organization, entity, company, or event. A case study involves deep understanding through various types of research data analysis techniques sources. Case studies can be an explanation, exploration, or describe an event. Data collection techniques in this research are observation, interviews (in-depth interviews), and documentation. The subjects in this research were caregivers, administrators and students. Meanwhile, the object is the Tebuireng Jombang Islamic Boarding School, East Java province. Data analysis techniques include data reduction, data display and drawing conclusions. The results of research at the Tebuireng Jombang Islamic boarding school have implemented a transformative leadership model while maintaining local wisdom to continue to strengthen organizational capacity for change quite well.